A New History of Modern India: an outline - Chakrabarti, Ranjan (Delhi: Surjeet Publications, 2019)
This is an introductory text that provides a well-rounded historical account of the history of modern India. The book will be of use to school and university students, teachers, competitive examinees and general readers who require a clear and concise delineation of Modern South Asian History.
Includes bibliographical references ( p. 415 - 416) , highlights the memorable dates and events ( p. 406 - 414 ) , Quotable quotes ( p. 414 ) and Exercises [ I. Essay- type questions ( p. 417 - 425 ) II. Objective-questions ( p. 425 - 429 ) ].
Keywords: HISTORY -- MODERN -- INDIA